Nonlinear coupling induced toroidal structure of edge localized modes. (21st December 2017) - Mink, A.F.; Hoelzl, M.; Wolfrum, E.; Orain, F.; Dunne, M.; Lessig, A.; Pamela, S.; Manz, P.; Maraschek, M.; Huijsmans, G.T.A.; Becoulet, M.; Laggner, F.M.; et al.
Abstract: Edge localized modes (ELMs) are magnetohydrodynamic (MHD) instabilities that cause fast periodic relaxations of the strong edge pressure gradient in tokamak fusion plasmas. A novel diagnostic method allows the extraction of toroidal mode numbers, rotation velocities and spatial information during the ELM cycle including the crash. While mode number branches n = 3 –6 and n = 8 –10 are dominant just before the ELM crash, during the ELM crash n = 2 –5 are observed in typical discharges with type-I ELMs in the tokamak experiment. These findings are compared to results from nonlinear MHD simulations. Although n = 6 is linearly dominant, nonlinear coupling in which n = 1 is particularly important leads to the dominance of n = 3 –5 during the ELM crash, in excellent agreement with experimental observations. The simultaneous occurrence of these modes over a wide radial region leads to high stochasticity and thus increased transport.